Optimised reduction of surgical gloves pinholes using forward search method - Ahmad, Azimah; Mohamed @ A.Rahman, Nur Anisah; Wahid, Zaharah (The National University of Malaysia (UKM), 2021)
This research investigates the factors during manufacturing process that affect the existence of pinholes in surgical gloves. The effects of eight variables on the number of pinholes were identified to determine the optimal condition to reduce the defects. Since there are multiple variables, a two-level fractional factorial design 28-4 were used to study the main effects and the first order interactions of the multiple variables. A multiple linear regression is used to model the data. This paper also examines the presence of influential points in the data using influential measures in linear regression such as Cook’s Distance, DFFITS, DFBETAS, Studentized Residual, Standardised Residual and Hadi's as well as the robust forward search. The impact of influential points is further assessed through deletion of potential influential points and model selection using adjusted R2, information criterion and stepwise selection to see whether influential points that significantly change the fit of the model exist.